The Functionalization of Miniature Energy‐Storage Devices. Issue 9 (9th August 2017) - Zhang, Longsheng; Liao, Meng; Bao, Luke; Sun, Xuemei; Peng, Huisheng
Abstract : In addition to fabricating miniaturized but high‐performance energy‐storage devices, integrating them with additional intelligent functions is also of great significance to accelerate the development of portable and wearable electronics. The integration of functional materials into energy‐storage devices can endow them with impressive properties besides energy storage, allowing many unprecedented applications to be possible. Here, the recent progress and methodology of constructing functionalized miniature energy‐storage devices that can change color, memorize shapes, and self‐heal are summarized. The strategies in the integration of different functions and the performances of these intelligent energy‐storage devices are then highlighted. The remaining challenges and future directions are provided in conclusion. Abstract : The recent advances in constructing functionalized miniature energy‐storage devices, including the integration of electrochromic, shape‐memory, and self‐healing functions, are highlighted. State‐of‐art examples, the strategies and methodologies of device fabrication, and the challenges and future directions of these smart multifunctional energy‐storage devices are presented.